Emergence of Food Matters in Val Poschiavo (Switzerland) through the Definition of a Regional Transition Project - Marjolaine Gros-Balthazard (Revue de Géographie Alpine)
Mountain regions are currently faced with a dual environmental and socioeconomic challenge. As markers of climate change, their transition is often examined from the tourism perspective (François et al., 2010). However, these regions are also places where people live and work, involving cross-cutting residential, productive, agricultural, energy-related and other strategies, which can provide leverage for their transition towards greater sustainability. Based on the empirical analysis of the 100% Valposchiavo initiative, implemented in the valley of the same name, this paper aims to contribute to reflections on potential food-related transition strategies for mountain regions. In this Italian-speaking valley located within the German-speaking Swiss Canton of Graubünden (Grisons), the 100% Valposchiavo initiative, aimed at promoting local organic production, has gradually become a regional project. Through the processes underlying the initiative, this example shows how food matters, not initially explicitly addressed in the agricultural project, and subsequently promoted through the branding of local product through the tourism sector, are ultimately emerging from the initiative, even though not all food-related challenges are addressed.